Identification of differentially accumulating pistil proteins associated with self‐incompatibility of non‐heading Chinese cabbage. (15th April 2013) - Wang, L.; Peng, H.; Ge, T.; Liu, T.; Hou, X.; Li, Y.; Whelan, J.
Abstract Non‐heading Chinese cabbage (Brassica campestris L. ssp. chinensis Makino), an important vegetable crop in China, exhibits a typical sporophytic self‐incompatibility (SI) system. To better understand the mechanism of SI response and identify potential candidate proteins involved in the SI system of this vegetable crop, the proteomic approach was taken to identify differential accumulating pistil proteins. Pistils were collected at 0 h and 2 h after self‐pollination at anthesis in self‐incompatible and compatible lines of non‐heading Chinese cabbage, and total proteins were extracted and separated by two‐dimensional gel electrophoresis (2‐DE). A total of 25 protein spots that displayed differential abundance were identified by matrix‐assisted laser desorption/ionisation‐time of flight mass spectrometry (MALDI–TOF/TOF MS) and peptide mass fingerprinting (PMF). Among them, 22 protein spots were confidently established. The mRNA levels of the corresponding genes were detected by quantitative RT‐PCR. The 22 identified protein spots are involved in energy metabolism (four), protein biosynthesis (three), photosynthesis (six), stress response and defence (five), and protein degradation (four). Among these potential candidate proteins, UDP‐sugar pyrophosphorylase could be involved in sucrose degradation to influence pollen germination and growth. Glutathione S–transferases could be involved in pollen maturation, and affect pollen fertility. Senescence‐associated cysteine protease, which is related to programmed cell death, could be mainly related to self pollen recognition of non‐heading Chinese cabbage. The study will contribute to further investigations of molecular mechanism of sporophytic SI in Brassicaceae.